Near infrared techniques applied to analysis of wheat-based products: Recent advances and future trends - Badaró, Amanda Teixeira; Hebling e Tavares, João Pedro; Blasco, José; Aleixos, Nuria; Barbin, Douglas Fernandes (Elsevier, 2022)
Wheat flour is a food ingredient used in different processed food products, including pasta, cake, bread, among others. Therefore, the authentication and assurance of good quality are of great importance. Traditional techniques used for quality parameters determinations are laborious, destructive, and demand chemical analysis. Hence, it is necessary the development of techniques capable to overcome these disadvantages. Spectral techniques are rapid, non-destructive, and chemical-free. This review approaches the applications of Near Infrared (NIR) Spectroscopy, Fourier Transform Near-Infrared (FT-NIR) Spectroscopy, and Hyperspectral Imaging (HSI) in wheat flour and wheat-based products authentication and assessment of quality parameters, composition, and contamination. Considering the need from the processing industry for a rapid analysis, moving the bench-top analytical system to the production line, future studies can explore in/on-line applications of these techniques for industrial processing lines and compare the use of handheld and benchtop spectrometers in these applications.